ChromID® CARBA Agar Fails to Detect Carbapenem-Resistant Enterobacteriaceae With Slightly Reduced Susceptibility to Carbapenems - Pauly, Natalie; Hammerl, Jens A.; Grobbel, Mirjam; Tenhagen, Bernd-Alois; Käsbohrer, Annemarie; Bisenius, Sandra; Fuchs, Jannika; Horlacher, Sabine; Lingstädt, Holger; Mauermann, Ute; Mitro, Silke; Müller, Margit; et al. (Frontiers in Microbiology, 2020)
After first detections of carbapenemase-producing Enterobacteriaceae (CPE) in animals, the European Union Reference Laboratory for Antimicrobial Resistance has provided a protocol for the isolation of carbapenemase-producing Escherichia (E.) coli from caecum content and meat. Up to now, only few isolates were recovered using this procedure. In our experience, the choice of the selective agar is important for the efficacy of the method. Currently, the use of the prevailing method fails to detect CPE that exhibit a low resistance against carbapenems. Thus, this study aims to evaluate the suitability of selective media with antibiotic supplements and commercial chromID® CARBA agar for a reliable CPE detection. Carbapenem-resistant isolates exhibiting a serine-based hydrolytic resistance mechanism (e.g. blaKPC enzymes) were consistently detected over 25 weeks on the different media. In contrast, carbapenemase-producers with only slightly reduced susceptibility and exhibiting a zinc-catalysed activity (e.g. blaVIM, blaNDM and blaIMP) could only be cultivated on long time expired chromID® CARBA, but within the whole test period on McC+CTX+MEM. Thus, chromID® CARBA agar appears to be not suitable for the detection of CPE with slightly increased minimum inhibitory concentrations (MIC) against carbapenems, which have been detected in German livestock and thus are of main interest in the national monitoring programs. Our data are in concordance with the results of eleven state laboratories that had participated in this study with their chromID® CARBA batches routinely used for the German CPE monitoring. Based on the determined CPE detection rate, we recommend the use of McC+CTX+MEM for monitoring purposes. This study indicates that the use of chromID® CARBA agar might lead to an underestimation of the current CPE occurrence in food and livestock samples.